THE USE OF GENETIC RESOURCES IN BREEDING OF VEGETABLE AND MELON CROPS - V. I. Burenin; T. M. Piskunova; Z. S. Vinogradov (Овощи России)
The analysis of the modern homeland assortment of vegetable crops is given. The donors of the most important traits and the accessions  of vegetable and melon crops perspective for breeding from the VIR collection are shown. The short characteristic of the varieties is given.